Predictive fish yield models for lakes and reservoirs of the Philippines, Sri Lanka and Thailand - Moreau, Jacques (FAO, 1991)
In parallel with the growth in the number of reservoirs in the contries of Asia and the larger Indo-Pacific islands, the need for fish yield prediction models has becom increasingly apparent, placing it among the priority areas of fishery research.